2002
DOI: 10.1111/j.1471-0528.2002.01046.x
|View full text |Cite
|
Sign up to set email alerts
|

Low dose acetylsalicylic acid in prevention of pregnancy‐induced hypertension and intrauterine growth retardation in women with bilateral uterine artery notches

Abstract: Objective To evaluate the efficacy of low‐dose acetylsalicylic acid in the prevention of pregnancy‐induced hypertension and intrauterine growth retardation in high‐risk pregnancies as determined by transvaginal Doppler ultrasound study of the uterine arteries at 12 to 14 weeks of gestation. Design Randomised, double blind and placebo‐controlled trial. Setting The Department of Obstetrics and Gynaecology, Tampere University Hospital, Finland. Population One hundred and twenty pregnant wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(53 citation statements)
references
References 23 publications
2
47
0
4
Order By: Relevance
“…9,27 A growing body of evidence points out a defect in early trophoblastic invasion and a failure to convert the spiral arteries into low resistance channels resulting in several obstetrical complications such as miscarriages, pre-eclampsia, IUGR, preterm labor, premature rupture of membranes (PROM), and SGA. 4,5,12,13,24,25 Anatomic findings such as thinner and fragmented trophoblastic shell and reduced cytotrophoblastic invasion of the lumen at the tip of the spiral arteries may be associated with premature onset of maternal circulation in cases of early pregnancy failure. Trophoblastic invasion seems to be defective in molar pregnancies as well.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…9,27 A growing body of evidence points out a defect in early trophoblastic invasion and a failure to convert the spiral arteries into low resistance channels resulting in several obstetrical complications such as miscarriages, pre-eclampsia, IUGR, preterm labor, premature rupture of membranes (PROM), and SGA. 4,5,12,13,24,25 Anatomic findings such as thinner and fragmented trophoblastic shell and reduced cytotrophoblastic invasion of the lumen at the tip of the spiral arteries may be associated with premature onset of maternal circulation in cases of early pregnancy failure. Trophoblastic invasion seems to be defective in molar pregnancies as well.…”
Section: Discussionmentioning
confidence: 97%
“…A correlation between uterine artery blood flow measured by Doppler sonography in early pregnancy and the subsequent development of pre-eclampsia and IUGR has been suggested in various studies. 13,[23][24][25] Additionally, it was indicated that measurements of uterine artery RI at 10-14 weeks' gestation were repeatable and reproducible. 26 Other studies concluded that birth weight correlated with early pregnancy uterine artery RI.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, only five studies on a combined total of 556 women were included in the final analysis because they fulfilled the three entry criteria: (1) treatment with aspirin or placebo initiated at or before 16 weeks of gestation, (2) information provided on preterm and term preeclampsia, and (3) judged for low-risk or unclear risk of bias. The control group received placebo in three of these studies and no treatment in two (table 1) [21,22,23,24,25]. …”
Section: Resultsmentioning
confidence: 99%
“…Eclampsia was found more in age group 20 to 29 years which accounted for 60.5% of eclamptic patients at Ilorin in Nigeria (Jimoh et at., 2007) and occurring more in primigravidae and more during wet season than dry season (Orji et al, 2007). Since there is currently no known measure to effectively and consistently prevent pre-eclampsia, early detection is critical in reducing the morbidity and mortality due to this condition (Duley, 2003;Hofmeyr et al, 2003;Vainia et al, 2002).…”
Section: Discussionmentioning
confidence: 99%